Boosting Students’ Motivation with Google Apps for Education - Варенко, Тетяна Костянтинівна (Проблеми сучасної освіти, 2018)
The paper is an outline of how different Google Apps for Education can be used to boost students’ motivation to study and improve their performance. It particularly focuses on the use of Google Classroom, Blogger, Google Drive, Google Sites, Google+, Google Calendar, which allow to hone students’ professional skills and deepen their knowledge while enabling them to produce real-life outputs of their educational activity that will be of use to them in their future professional development. And these outputs are primarily what motivate the students to do the best job they can when completing the assignments.